Economic growth under Solow-neutrality. Issue 1 (1st January 2021) - Mert, Merter
Abstract: This study is the first attempt to measure growth depending on the equation of the concave production possibility frontier, under Solow-neutrality. Although there is evidence that the nature of technological progress is Solow-neutral, Solow-neutrality is not compatible with the steady-state. This study solves that contradiction. To do this, we make three simple contributions. First, the natural rate of growth has been explained in harmony with the economic concepts such as constant returns to scale, full capacity and steady-state, under Solow-neutrality. Secondly, the equation of the concave production possibility frontier has been obtained when the nature of technological progress is Solow-neutral. Thirdly, economic growth has been explained based on the equation of the concave production possibility frontier, under Solow-neutrality. According to the first result of the study, Solow-neutrality becomes compatible with the long-run equilibrium growth and the steady-state under specific conditions. According to the second result of the study, positive economic growth occurs under specific conditions.